A middle Albian biota (Algae, Foraminifera and Gastropoda) from Ahuacatlán, State of Querétaro, Mexico - Blanca Estela Buitrón-Sánchez; Miguel Carrillo-Martínez; María del Carmen Rosales-Domínguez; Noemí Aguilera-Franco (Revista Mexicana de Ciencias Geológicas)
In the northeastern part of the State of Querétaro, central Mexico, Cretaceous carbonate rocks are extensively exposed… in order to continue, download the full paper in PDF.